Morphostructure Control Towards the Development of Mahawu Volcanic Complex, North Sulawesi - S. Poedjoprajitno (Indonesian Journal on Geoscience, 2012)
DOI: 10.17014/ijog.v7i1.134The studied area, situated in northeastern part of North Sulawesi Arm, is dominantly occupied by the Mahawu, Linau, Tompusu, and Kasurutan volcanic rocks. Using remote sensing data, such as landsat image, black and white panchromatic aerial photograph, and IFSAR image, morphology-origin unit and morphology lineament can be interpreted. Four morphology-origin units, those are Mahawu Volcano Complex, Intra-montane Plain structure, Linau Volcano Complex, and Lacustrine Plain are recognized. Furthermore, morphological lineament pattern was statistically processed to find out the general stress direction in the area to determine the probability of the structural morphology occurrence in the Mahawu Volcano Complex. The result shows that generally the development pattern of volcanic cones are irregular, except the Mahawu Volcano Complex showing a linear pattern. This lineament pattern is interpreted as a NW - SE fault pattern controlling the rise of magma. At least, two tectonic and two eruption periods occurred regularly at different time from the Quaternary age till the present.